2013
DOI: 10.2527/jas.2012-6067
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for scrotal circumference, breeding soundness examination and sperm defects in young Nellore bulls

Abstract: A total of 51,161 records of scrotal circumference measurements at 18 mo of age (SC18) and 17,648 records of sperm defects and breeding soundness of Nellore bulls (mean age of 22.5 mo), raised under extensive conditions, were analyzed to estimate coefficients of heritability and genetic correlations of morphological semen traits by Bayesian inference. The observed semen traits were classified as minor (MID), major (MAD), and total sperm defects (TD). The animals were classified according to breeding soundness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
3
15
1
1
Order By: Relevance
“…Vale Filho et al (1986) observed higher averages for low fertility and infertility (42.00 and 40.50%, respectively) in a centre performing artificial insemination of Bos taurus indicus bulls that were used as reproducers in extensive creation herds. Results similar to those of the present study were recorded by Silveira et al (2010), who found that 18.11% and 3.56% of animals were unsound for reproduction and discarded, respectively, on average; Silva et al (2013) found that 11.54% of animals were unsound (including animals that were unsound for reproduction and discarded animals) in the same herd.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Vale Filho et al (1986) observed higher averages for low fertility and infertility (42.00 and 40.50%, respectively) in a centre performing artificial insemination of Bos taurus indicus bulls that were used as reproducers in extensive creation herds. Results similar to those of the present study were recorded by Silveira et al (2010), who found that 18.11% and 3.56% of animals were unsound for reproduction and discarded, respectively, on average; Silva et al (2013) found that 11.54% of animals were unsound (including animals that were unsound for reproduction and discarded animals) in the same herd.…”
Section: Discussionsupporting
confidence: 91%
“…The results presented in Table 1 are superior to the results presented by Salvador (2001) and Dias et al (2006), who found that 40.2 and 26.3% of sexually mature 2-year-old animals belonged to the Nellore race. However, the sexual maturity values reported in this study were close to the values recorded by Silveira et al (2010) (78.33%) and Silva et al (2013) (88.46%), which were obtained for animals of the Nellore race from the same herd.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This issue is especially important since artificial insemination is not only one of the most important tools to improve pregnancy rates, but also a tool for effective selection due to the use of the most valuable breeders (5). A number of factors including genetic background, age, varying quality of feed, environmental and specific climatic conditions affecting sperm quality (6)(7)(8). In bull sires, an evaluation of sperm fertilizing capability always includes determination of sperm concentration, motility and morphology, i.e.…”
mentioning
confidence: 99%